A case study about intensive music therapy process with a depressed client in late adulthood - Allinen, Anna (2013)
Depression is a common illness with over 350 million people suffering from it worldwide. Transitional periods in life, such as the retirement process, can make people especially vulnerable to developing depressive illnesses.